OPTIMIZING EMPLOYEE EFFECTIVENESS: A STUDY OF THE RELATIONSHIP BETWEEN JOB SATISFACTION AND DEPARTMENTAL PERFORMANCE - Dalila, Margaretha H.; Tui, Fenti Prihatini Dance; Tantu, Romy (Universitas Negeri Gorontalo, 2024)
This study aims to find out. the effect of job satisfaction on the effectiveness of employee work at the Department of Cooperatives, SMEs, Industry and Trade of Gorontalo Province. The approach in this study is quantitative with ex-post facto methods. Data collection in this study was carried out by questionnaire. The number of samples was 82 people obtained by the saturated sampling process. Data analysis in this study is a simple linear regression inferential quantitative analysis. The results showed that job satisfaction had a positive and significant effect on the effectiveness of employee work at the Gorontalo Provincial Industry and Trade SME Cooperative Office by 38.10%. The influence of other variables on employee work effectiveness amounted to 61.90%, namely employee competence variables, career management, employee capacity development, leadership, work climate, work experience, and supervision at work. Positive results show that employees at the Department of Cooperatives, SMEs, Industry and Trade of Gorontalo Province, the more satisfied they are with the work they are responsible for, the higher the achievement of the effectiveness of the employee's work.